Potensi Usaha Mikro Kecil Menengah Iggo Kuliner Jambi Dalam Meningkatkan Halal Food Di Kota Jambi - Nurfitri Martaliah; Titin Agustia Ningsih; Saslina Saslina (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to find out the potential for developing Halal Food by Jambi Iggo Culinary UMKM, as well as to find out the obstacles faced by Jambi Iggo Culinary UMKM in implementing Halal Food, this research is of a qualitative type. The objects of this research are the owners, employees and regular consumers of UMKM Iggo Culinary Jambi. The data sources used are primary data and secondary data. Data were obtained directly from 15 respondents using data analysis methods, namely observation, interviews and personal documentation, then the data was processed using data processing techniques. The results showed that: In carrying out the potential for developing halal food, UMKM Iggo Culinary Jambi carried out four items that became indicators of the success of UMKM Iggo Culinary Jambi, namely as follows, Increasing the components of food products used, Increasing diversity in production, Increasing distribution and supply of products (halal logistics), Increasing the balance of product composition, In implementing the development potential carried out by UMKM Iggo Culinary Jambi, there are obstacles faced by UMKM Iggo Culinary Jambi, along with the obstacles: Lack of availability of product food ingredients, Unfair competition , There are suppliers who commit fraud against the halal logo on the product.